Parental Decisions on Sharing Their Children's Private Information on Social Media among Families in Jakarta Area - Wardhani, Putri; Sekarasih, Laras (Makara Human Behavior Studies in Asia, 2021)
The practice of publishing photos and videos containing children’s private information on social media—also known assharenting—is popular among parents in Jakarta. Embarking from the debate about privacy paradox in which it is believed that privacy concern does not predict someone’s behaviors in managing his/her private information online, this research tries to reveal the considerations underlying parental decisions when sharing their children’s private information through social media and their perceived risk toward their children’s online safety. Using qualitative approach, the researcher conducted interviews with 20 parents in Jakarta with at least one child younger 13 year old. The result suggests that the perceived benefit of sharenting exceeds its perceived risks. The study also found four reasons why parents exercise sharenting: to document their children’s development, to gain social support from their followers on social media, to overcome loneliness as a new parents and the low self-efficacy of parents in protecting children’s privacy on the internet. Unsurprisingly sharenting through social media has become a growing trend among parents. This finding thus will be useful as a groundwork to develop an intervention program with regards to relevant sharenting in the context of Jakarta, Indonesia.